Anisotropic plasticity‐damage material model for sheet metal — Regularised single surface formulation - Friedlein, J.; Mergheim, J.; Steinmann, P. (PAMM)
Sheet metal forming as well as mechanical joining demand increasingly accurate and efficient material modelling to capture large deformations, the inherent sheet orthotropy and even process-induced damage, which is expected to be influential. To account for large strains the additive logarithmic strain space is utilised that enables a straightforward incorporation of plastic anisotropy, herein modelled by a Hill48 yield function. A gradient-enhancement is used to equip the ductile damage model with an internal length scale curing the damage-induced localisation. An affine combination of the local and non-local softening variable is derived enabling a more efficient single surface formulation for the regularised plasticity-damage material model.

Further development of a numerical method for analyzing the load capacity of clinched joints in versatile process chains - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson

Numerical and experimental investigation of the transmission moment of clinching points - Steinfelder, C.; Kalich, J.; Brosius, A.; Füssel, U. (IOP Conference Series: Materials Science and Engineering)
In clinching, the combinations of requirements, materials, component dimensions and tools influence the resulting joint geometry and the resulting bonding mechanisms. These in turn affect the property profile of the joint. For example, it is possible to use different tools to flexibly adapt clinching points to the respective required load regime. Clinching points dimensioned in this way can be geometrically similar, but have different mechanical stress states, which leads to different properties in terms of load-bearing behavior. Within the scope of this work, the clinching process with different tools in optimal and compromise design and its effect on the force and form-closure component, is investigated in a torsion test of the clinched connection. Clinched steel sheets with two thicknesses and joining directions are analyzed. Virtual experiments are carried out using finite element analyses (FEA) of the joining process and are followed by a springback simulation. Subsequently, the surface pressure between the two joining partners in the clinching points is calculated on the basis of the results from the FEA and the transmittable moment of the connection, as an indicator for the force-closure component, is determined. Finally, the experimental and simulated data are compared and discussed.

Clinching of Thermoplastic Composites and Metals—A Comparison of Three Novel Joining Technologies - Gröger, B.; Troschitz, J.; Vorderbrüggen, J.; Vogel, C.; Kupfer, R.; Meschut, G.; Gude, M. (Materials)
Clinching continuous fibre reinforced thermoplastic composites and metals is challenging due to the low ductility of the composite material. Therefore, a number of novel clinching technologies has been developed specifically for these material combinations. A systematic overview of these advanced clinching methods is given in the present paper. With a focus on process design, three selected clinching methods suitable for different joining tasks are described in detail. The clinching processes including equipment and tools, observed process phenomena and the resultant material structure are compared. Process phenomena during joining are explained in general and compared using computed tomography and micrograph images for each process. In addition the load bearing behaviour and the corresponding failure mechanisms are investigated by means of single-lap shear tests. Finally, the new joining technologies are discussed regarding application relevant criteria.

Computed tomography investigation of the material structure in clinch joints in aluminium fibre-reinforced thermoplastic sheets - Gröger, B.; Köhler, D.; Vorderbrüggen, J.; Troschitz, J.; Kupfer, R.; Meschut, G.; Gude, M. (Production Engineering)

Effect of Different Tool Geometries on the Mechanical Properties of Al-Al Clinch Joints - Ewenz, L.; Kalich, J.; Zimmermann, M.; Füssel, U. (Key Engineering Materials)
The use of clinch joints, e.g. vehicle structures, is determined by the reliability of the joint and its strength properties - in particular the fatigue strength. Clinch connections offer the advantage over form-closure and force-closure processes that they can also be used for hybrid material combinations. In order to be able to evaluate the influence of the geometry parameters such as e.g. undercut, neck thickness or also base thickness on the fatigue behavior, three clinch connections (in optimum and compromise design) with different tool parameters were designed and examined using the example of a joining task with aluminum sheet material. For this purpose, fatigue curves (F-N curves) in the range of high to very high numbers of load cycles (N = 105 to 107) were determined. In this load cycle range, a so-called "neck fracture" is mainly to be expected as the type of failure, whereas for quasi-static tests, a “buckling” is more likely to occur. The tests were carried out on single-cut overlapping shear tensile specimens. Metallographic and scanning electron microscopic examinations of the joints and the fracture surfaces served to identify the crack initiation site and to clarify the respective type of failure. Significant differences in the damage behaviour of the three clinching variants could be shown. This observation enables one step into the direction of fully understanding the relationship along the causal chain "joint requirements - joining process - fatigue strength". Thus the adaptability of the clinching process can be improved.

Modelling of thermally supported clinching of fibre-reinforced thermoplastics: Approaches on mesoscale considering large deformations and fibre failure - Gröger, B.; Hornig, A.; Hoog, A.; Gude, M. (ESAFORM 2021 - 24th International Conference on Material Forming)
Thermally supported clinching (Hotclinch) is a novel promising process to join dissimilar materials. Here, metal and fibre-reinforced thermoplastics (FRTP) are used within this single step joining process and without the usage of auxiliary parts like screws or rivets. For this purpose, heat is applied to improve the formability of the reinforced thermoplastic. This enables joining of the materials using conventional clinching-tools. Focus of this work is the modelling on mesoscopic scale for the numerical simulation of this process. The FTRP-model takes the material behaviour both of matrix and the fabric reinforced organo-sheet under process temperatures into account. For describing the experimentally observed phenomena such as large deformations, fibre failure and the interactions between matrix and fibres as well as between fibres themselves, the usage of conventional, purely Lagrangian based FEM methods is limited. Therefore, the combination of contact-models with advanced modelling approaches like Arbitrary-Lagrangian-Eulerian (ALE), Coupled-Eulerian-Lagrangian (CEL) and Smooth-ParticleHydrodynamics (SPH) for the numerical simulation of the clinching process are employed. The different approaches are compared with regard to simulation feasibility, robustness and results accuracy. It is shown, that the CEL approach represents the most promising approach to describe the clinching process.

A finite plasticity gradient-damage model for sheet metals during forming and clinching - Friedlein, J.; Mergheim, J.; Steinmann, P. (Key Engineering Materials)
In recent years, clinching has gathered popularity to join sheets of different materials in industrial applications. The manufacturing process has some advantages, as reduced joining time, reduced costs, and the joints show good fatigue properties. To ensure the joint strength, reliable simulations of the material behaviour accounting for process-induced damage are expected to be beneficial to obtain credible values for the ultimate joint strength and its fatigue limit. A finite plasticity gradient-damage material model is outlined to describe the plastic and damage evolutions during the forming of sheet metals, later applied to clinching. The utilised gradient-enhancement cures the damage-induced localisation by introducing a global damage variable as an additional finite element field. Both, plasticity and damage are strongly coupled, but can, due to a dual-surface approach, evolve independently. The ability of the material model to predict damage in strongly deformed sheets, its flexibility and its regularization properties are illustrated by numerical examples.

Temperature dependent modelling of fibre-reinforced thermoplastic organo-sheet material for forming and joining process simulations - Gröger, B.; Hornig, A.; Hoog, A.; Gude, M. (Key Engineering Materials)
Joining and local forming processes for fibre-reinforced thermoplastics (FRTP) like hole-forming or variations of the clinching process require an in-depth understanding of the process induced effects on meso-scale. For numerical modelling with a geometrical description of a woven fabric, adequate material models for a representative unit cell are identified. Model calibration is achieved employing a mesoscopic finite-element-approach using the embedded element method based on tensile tests of the consolidated organo-sheets and a phenomenological evaluation of photomicrographs. The model takes temperature dependent stiffness and fibre tension failure into account.

Parametric FEM for computational homogenization of heterogeneous materials with random voids - Pivovarov, Dmytro; Mergheim, Julia; Willner, Kai; Steinmann, Paul (PAMM)
Computational homogenization is a powerful tool which allows to obtain homogenized properties of materials on the macroscale from the simulation of the underlying microstructure. The response of the microstructure is, however, strongly affected by variations in the microstructure geometry. The effect of geometry variations is even stronger in cases when the material exhibits plastic deformations. In this work we study a model of a steel alloy with arbitrary distributed elliptic voids. We model one single unit cell of the material containing one single void. The geometry of the void is not precisely known and is modeled as a variable orientation of an ellipse. Large deformations applied to the unit cell necessitate a finite elasto-plastic material model. Since the geometry variation is parameterized, we can utilize the method recently developed for stochastic problems but also applicable to all types of parametric problems — the isoparametric stochastic local FEM (SL-FEM). It is an ideal tool for problems with only a few parameters but strongly nonlinear dependency of the displacement fields on parameters. Simulations demonstrate a strong effect of parameter variation on the plastic strains and, thus, substantiate the use of the parametric computational homogenization approach.

Effect of Solidification Rates at Sand Casting on the Mechanical Joinability of a Cast Aluminium Alloy - Neuser, Moritz; Grydin, Olexandr; Andreiev, Anatolii; Schaper, Mirko (Metals)
Implementing the concept of mixed construction in modern automotive engineering requires the joining of sheet metal or extruded profiles with cast components made from different materials. As weight reduction is desired, these cast components are usually made from high-strength aluminium alloys of the Al-Si (Mn, Mg) system, which have limited weldability. The mechanical joinability of the cast components depends on their ductility, which is influenced by the microstructure. High-strength cast aluminium alloys have relatively low ductility, which leads to cracking of the joints. This limits the range of applications for cast aluminium alloys. In this study, an aluminium alloy of the Al-Si system AlSi9 is used to investigate relationships between solidification conditions during the sand casting process, microstructure, mechanical properties, and joinability. The demonstrator is a stepped plate with a minimum thickness of 2.0 mm and a maximum thickness of 4.0 mm, whereas the thickness difference between neighbour steps amounts to 0.5 mm. During casting trials, the solidification rates for different plate steps were measured. The microscopic investigations reveal a correlation between solidification rates and microstructure parameters such as secondary dendrite arm spacing. Furthermore, mechanical properties and the mechanical joinability are investigated.

Joining suitability of cast aluminium for self-piercing riveting - Neuser, Moritz; Kappe, Fabian; Busch, M; Grydin, Olexandr; Bobbert, Mathias; Schaper, Mirko; Meschut, Gerson; Hausotte, T (IOP Conference Series: Materials Science and Engineering)

Concept development of a method for identifying friction coefficients for the numerical simulation of clinching processes - Böhnke, Max; Rossel, Moritz Sebastian; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (The International Journal of Advanced Manufacturing Technology)
Abstract In order to reduce fuel consumption and thus pollutant emissions, the automotive industry is increasingly developing lightweight construction concepts that are accompanied by an increasing usage of aluminum materials. Due to poor weldability of aluminum in combination with other materials, mechanical joining methods such as clinching were developed and established in series production. In order to predict the relevant characteristics of clinched joints and to ensure the reliability of the process, it is simulated numerically during product development processes. In this regard, the predictive accuracy of the simulated process highly depends on the implemented friction model. In particular, the frictional behavior between the sheet metals as well as between the sheet metal and clinching tools has a significant impact on the geometrical formation of the clinched joint. No testing methods exist that can sufficiently investigate the frictional behavior in sheet materials, especially under high interface pressures, different relative velocities, and long friction paths, while allowing a decoupled consideration of the test parameters. This paper describes the development of further testing concepts based on a proven tribo-torsion test method for determining friction coefficients between sheet metal materials for the simulation of clinching processes. For this purpose, the correlation of interface pressure and the relative velocity between aluminum and steel sheet material in clinching processes is investigated using numerical simulation. Based on these findings, the developed concepts focus on determining friction coefficients at interface pressures of the above materials, yield stress, as well as the reproduction of the occurring friction conditions between sheet metal materials and tool surfaces in clinching processes using tool substitutes. Furthermore, wear investigations between sheet metal material and tool surface were carried out in the friction tests with subsequent EDX analyses of the frictioned tool surfaces. The developed method also allows an optical deformation measurement of the sheet metal material specimen by means of digital image correlation (DIC). Based on a methodological approach, the test setups and the test systems used are explained, and the functionality of the concepts is proven by experimental tests using different sheet metal materials.

Development of a Method for the Identification of Friction Coefficients in Sheet Metal Materials for the Numerical Simulation of Clinching Processes - Rossel, Moritz Sebastian; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
In order to reduce the fuel consumption and consequently the greenhouse emissions, the automotive industry is implementing lightweight constructions in the body in white production. As a result, the use of aluminum alloys is continuously increasing. Due to poor weldability of aluminum in combination with other materials, mechanical joining technologies like clinching are increasingly used. In order to predict relevant characteristics of clinched joints and to ensure the reliability of the process, it is simulated numerically during product development processes. In this regard the predictive accuracy of the simulated process highly depends on the implemented friction model. In particular, the frictional behavior between the sheet metals affects the geometrical formation of the clinched joint significantly. This paper presents a testing method, which enables to determine the frictional coefficients between sheet metal materials for the simulation of clinching processes. For this purpose, the correlation of interface pressure and the relative velocity between aluminum sheets in clinching processes is investigated using numerical simulation. Furthermore, the developed testing method focuses on the specimen geometry as well as the reproduction of the occurring friction conditions between two sheet metal materials in clinching processes. Based on a methodical approach the test setup is explained and the functionality of the method is proven by experimental tests using sheet metal material EN AW6014.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Influence of rivet length on joint formation on self-piercing riveting process considering further process parameters - Kappe, Fabian; Bielak, Christian Roman; Sartisson, Vadim; Bobbert, Mathias; Meschut, Gerson (ESAFORM 2021)
Driven by the CO2-emission law by the European government and the increasing costs for raw materials as well as energy, the automotive industry is increasingly using multi-material constructions. This leads to a continuous increase in the use of mechanical joining techniques and especially the self-piercing riveting is of particular importance. The reason for this is the wide range of joining possibilities as well as the high load-bearing capacities of the joints. To be able to react to changing boundary conditions, like material thickness or strength variation of the sheets, research work is crucial with regard to the increase of versatility. In this paper, a numerical study of the influences on the selfpiercing riveting process is presented. For this purpose, the influence of different process parameters such as rivet length and die depth on various quality-relevant characteristics were investigated. With the help of the design of experiment, significant influences were determined and interactions between the individual parameters are shown.

Influence of various procedures for the determination of flow curves on the predictive accuracy of numerical simulations for mechanical joining processes - Böhnke, Max; Kappe, Fabian; Bobbert, Mathias; Meschut, Gerson (Materials Testing)
The predictive quality of numerical simulations for mechanical joining processes depends on the implemented material model, especially regarding the plasticity of the joining parts. Therefore, experimental material characterization processes are conducted to determine the material properties of sheet metal and generate flow curves. In this regard, there are a number of procedures which are accompanied by varying experimental efforts. This paper presents various methods of determining flow curves for HCT590X as well as EN AW-6014, including varying specimen geometries and diverse hardening laws for extrapolation procedures. The flow curves thus generated are compared considering the variety of plastic strains occurring in mechanical joining processes. The material data generated are implemented in simulation models for the joining technologies, clinching and self-piercing riveting. The influence of the varied methods on the predictive accuracy of the simulation model is analysed. The evaluation of the differing flow curves is achieved by comparing the geometric formation of the joints and the required joining forces of the processes with experimentally investigated joints.

Computed tomography investigation of the material structure in clinch joints in aluminium fibre-reinforced thermoplastic sheets - Gröger, Benjamin; Köhler, Daniel; Vorderbrüggen, Julian; Troschitz, Juliane; Kupfer, Robert; Meschut, Gerson; Gude, Maik (Production Engineering)
Abstract Recent developments in automotive and aircraft industry towards a multi-material design pose challenges for modern joining technologies due to different mechanical properties and material compositions of various materials such as composites and metals. Therefore, mechanical joining technologies like clinching are in the focus of current research activities. For multi-material joints of metals and thermoplastic composites thermally assisted clinching processes with advanced tool concepts are well developed. The material-specific properties of fibre-reinforced thermoplastics have a significant influence on the joining process and the resulting material structure in the joining zone. For this reason, it is important to investigate these influences in detail and to understand the phenomena occurring during the joining process. Additionally, this provides the basis for a validation of a numerical simulation of such joining processes. In this paper, the material structure in a joint resulting from a thermally assisted clinching process is investigated. The joining partners are an aluminium sheet and a thermoplastic composite (organo sheet). Using computed tomography enables a three-dimensional investigation that allows a detailed analysis of the phenomena in different joining stages and in the material structure of the finished joint. Consequently, this study provides a more detailed understanding of the material behavior of thermoplastic composites during thermally assisted clinching.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Experimentelle bruchmechanische Untersuchung eines clinchgeeigneten Bleches aus HCT590X mithilfe einer neuen Probengeometrie - Weiß, Deborah; Schramm, Britta; Neuser, Moritz; Grydin, Olexandr; Kullmer, Gunter

Numerical analysis of the robustness of clinching process considering the pre-forming of the parts - Bielak, Christian Roman; Böhnke, Max; Beck, Robert; Bobbert, Mathias; Meschut, Gerson (Journal of Advanced Joining Processes.)
Keywords: Clinching; process simulation; FEM; pre-straining; sensitivity analysis

Characterization and Numerical Modelling of Through-Thickness Metallic-Pin-Reinforced Fibre/Thermoplastic Composites under Bending Loading - Böhm, H.; Zhang, H.; Gröger, B.; Hornig, A.; Gude, M. (Journal of Composites Science)